Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts